1982
DOI: 10.1037/0033-2909.92.3.547
|View full text |Cite
|
Sign up to set email alerts
|

Counting behavior in animals: A critical evaluation.

Abstract: In this article we present a critical evaluation of evidence bearing on the question of whether animals can count. A definition of counting is adopted from Gelman and Gallistel (1978) and Piaget (1952) that allows us to compare the form of counting behavior observed in animals with its counterpart in humans. The evidence, which ranges from early anecdotal reports to modern experimental analyses, suggests that a variety of infrahumans ranging from birds to primates can learn to count, although successful demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
132
3

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(143 citation statements)
references
References 70 publications
8
132
3
Order By: Relevance
“…This viewof the rat's countingcontrasts sharply with an earlier view proposed by Davis and Memmott (1982), who concluded that natural history has giventhe rat little reason to count, especially in "unnatural" settings.…”
Section: Discussioncontrasting
confidence: 53%
“…This viewof the rat's countingcontrasts sharply with an earlier view proposed by Davis and Memmott (1982), who concluded that natural history has giventhe rat little reason to count, especially in "unnatural" settings.…”
Section: Discussioncontrasting
confidence: 53%
“…Some researchers have argued that using number may be a "last-resort" strategy of quantification (Breukelaar and Dalrymple-Alford 1998; Davis and Memmott 1982) when other cues such as amount cannot be used (but see Brannon 2005a). These mechanisms of quantification have presumably evolved to enhance survival and successful reproduction of individuals in their natural environment, such as in foraging, inter-group conflict, parental investment, and predator avoidance contexts (Hamilton 1971;Kitchen 2004;Lyon 2003;McComb et al 1994;Wilson et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Counting, however, like other cognitive behaviors such as language, has often been defined to exclude nonhuman numerical competence (Davis & Memmott, 1982). The revitalization of studies of animal cognition has provided an emerging theoretical framework for examining the phylogenetic continuum of information processing (Hulse, Fowler, & Honig, 1978;Roitblat, Bever, & Terrace, 1984).…”
mentioning
confidence: 99%